1981
DOI: 10.1002/ana.410100506
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immunity in myasthenia gravis: Biochemical characterization of acquired antireceptor antibodies and clinical correlations

Abstract: The titer and characteristics of antiacetylcholine receptor antibody (AChR-Ab) were investigated in 184 patients with myasthenia gravis. Mean AChR-Ab titers of each clinical grade increased with the severity of the disease. AChR-Ab was always of an IgG class. IgM (5 of 92) and IgA (2 of 48) class AChR-Ab were detected, but only concurrently with IgG and in low concentrations. IgG subclass 3 was not prominent. In 3 patients with AChR-Ab titers in the normal range, blockade of bungarotoxin binding to receptor co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…Moreover, in all but 1 patient the clinical relapse was preceded by a rise of the antibody titer. This further supports the notion that the intraindividual correlation among patients between the serum autoantibody concentration and the clinical severity of the disease is usually good [ S , 28,[30][31][32]. After reinstitution of immunosuppressive treatment, the elevated titers declined slowly, approaching the pretreatment levels.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, in all but 1 patient the clinical relapse was preceded by a rise of the antibody titer. This further supports the notion that the intraindividual correlation among patients between the serum autoantibody concentration and the clinical severity of the disease is usually good [ S , 28,[30][31][32]. After reinstitution of immunosuppressive treatment, the elevated titers declined slowly, approaching the pretreatment levels.…”
Section: Discussionsupporting
confidence: 78%
“…[21][22][23][24] Herein, in a large group of patients with MG, including SNMG, studied at the time of SFEMG, we found a correlation between jitter values and AChR-Ab titers and clustered AChR-Abs in patients with SNMG. The correlation of complement-fixing capacity with neuromuscular jitter was greater, again supporting the likely importance of the complement system in the pathogenesis of AChR-Ab-positive MG.…”
mentioning
confidence: 99%
“…Both laboratory tests are highly sensitive in the diagnosis of MG, 10,11,18,21,22,24 but previous studies have not shown a clear relationship between the degree of abnormality and the clinical severity, presentation, or prognosis of myasthenia. Strong correlations between the mean AChR antibody titers and the clinical severity of disease in groups of MG patients have been reported previously, 14,23 but the absolute AChR antibody titer is often of limited value in predicting the nature of disease progression or its prognosis. Nevertheless, clinical improvement after plasma exchange may be associated with a fall in titer in individual patients.…”
Section: Myasthenia Gravis (Mg) Is An Immune-mediatedmentioning
confidence: 81%